2011
DOI: 10.1007/s11195-011-9233-5
|View full text |Cite
|
Sign up to set email alerts
|

Marital Relationship and Quality of Life Among Couples with Infertility

Abstract: The study was conducted due to the fact that there is not enough data on the topic in Turkey, where having a child brings status to women, and the related literature includes no qualitative studies about the effects of infertility on marital relationship (MR) and Quality of Life (QoL). Qualitative research in which 16 people who received successful infertility treatment received in-depth interviews, and data collected retrospectively. Infertility has negative effects on MR and QoL. In the marital relation cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
1
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 26 publications
4
58
1
8
Order By: Relevance
“…Some involuntarily childless women internalised pronatalism, perceiving themselves as failures and incomplete (Bell, 2013;Sternke & Abrahamson, 2015). There is, however, limited research investigating the exclusion of childless women in their reproductive years from the social domain, which encompasses social networks, support and interaction, and social and leisure participation (see for example, Albertini & Mencarini, 2014;Bell, 2013;Debest & Mazuy, 2014;Doyle, Pooley, & Breen, 2013;McNamee & James, 2012;Sternke & Abrahamson, 2015), the service domain, which incorporates availability, accessibility, affordability, appropriateness and adequacy of services (see for example Baker, 2003;Hammarberg, Astbury, & Baker, 2001;Mollen, 2006;Onat & Beji, 2012;Parry, 2004) and the economic domain, including participation in employment, the nature and quality of working lives, and material and financial resources (see for example Doyle et al, 2013;Fieder, Huber, & Bookstein, 2011;Huber, Bookstein, & Fieder, 2010;Malik & Coulson, 2013;Rich et al, 2011). There is no existing research in the civic domain, which includes participation in community and political activities, groups and organisations.…”
Section: Introductionmentioning
confidence: 99%
“…Some involuntarily childless women internalised pronatalism, perceiving themselves as failures and incomplete (Bell, 2013;Sternke & Abrahamson, 2015). There is, however, limited research investigating the exclusion of childless women in their reproductive years from the social domain, which encompasses social networks, support and interaction, and social and leisure participation (see for example, Albertini & Mencarini, 2014;Bell, 2013;Debest & Mazuy, 2014;Doyle, Pooley, & Breen, 2013;McNamee & James, 2012;Sternke & Abrahamson, 2015), the service domain, which incorporates availability, accessibility, affordability, appropriateness and adequacy of services (see for example Baker, 2003;Hammarberg, Astbury, & Baker, 2001;Mollen, 2006;Onat & Beji, 2012;Parry, 2004) and the economic domain, including participation in employment, the nature and quality of working lives, and material and financial resources (see for example Doyle et al, 2013;Fieder, Huber, & Bookstein, 2011;Huber, Bookstein, & Fieder, 2010;Malik & Coulson, 2013;Rich et al, 2011). There is no existing research in the civic domain, which includes participation in community and political activities, groups and organisations.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of its impacts on the couple's relationship, studies have reported that infertile couples had a lower level of marital satisfaction than their fertile counterparts [4,5]. A study conducted in China indicated that women seeking IVF treatment were more likely than fertile women to report that their marriage was unstable [6].…”
Section: Introductionmentioning
confidence: 99%
“…Family formation can increase social and economic status of people in collectivistic cultures [38]. Voluntary childlessness is not socially acceptable in such a culture [19]. On the other hand, in an individual culture, there is a high value on the freedom and happiness of an individual, self and autonomous individual are highly emphasized [39].…”
Section: A Cross-cultural Study About Positive and Negative Emotions mentioning
confidence: 99%
“…The term infertility may be perceived clinically as a medical condition with no inclusion of psychological and social aspects [15]. However, there are studies indicating that infertility is experienced as a social and psychological phenomenon as well [16,17] and affects both social functioning [18,19] and psychological well-being [20]. Parenthood is a major transition in adult life for both men and women.…”
Section: A Cross-cultural Study About Positive and Negative Emotions mentioning
confidence: 99%